Avaliação da transição do índice de rendimento mínimo IR3 para IR4 no Brasil para motores de indução trifásicos até 10 CV - Paiva, Gabriel Augusto Duarte de (Universidade Federal Rural do Semi-Árido, 2019)
Since 1984 Brazil has been concerned with energy saving and high quality products in the market. In this year INMETRO brought up a discussion, which has led up to the Brazilian Labeling Program (PBE), which at the end of 2001 with the Law No. 10.295, ended up making the "seals" of energy efficiency mandatory. From then on the concern about energy economy and efficiency has just increased, today, the country, is facing the “aegis” of the 2030 National Energy Plan, which predicts 53000 GWh of savings through incentives. In 2002 came the first minimum energy performance standards in Brazil: IR1 and IR2 known as standard and high efficiency motors. Similar indexes for these types of motors had been previously defined by the International Electrotechnical Commission, IEC. In 2005 Interministerial Ordinance No. 553 gave a deadline for the manufacture and marketing of standard motors. Finally, in 2017 Interministerial Ordinance No. 1 determined that IR3 motors should be the only circulating engines in the market until mid-2020. The main objective of this work is to analyze the decreasing of losses between indexes to characterize a new IR4 index and in addition it is also an objective the comparison between the 2030 National Energy Efficiency Plan (PNEF 2030) target, with the energy saved by the index implementation in 2030. Through an equation defined by Procel with UNIFEI, to calculate the energy consumption of a motor population, the year-to-year consumption of the IR3 and IR4 engines was defined separately from 2019 to 2030. The application of the equation depended on the demand forecast made for 2013, considering a seasonal and trend behavior of the sales data obtained.. The new yields were calculated from replicating “average” behavior of the percentage decreases in losses for index transitions. The analysis consisted of comparing motor consumption in two situations, the first in which only IR3 engines are being sold, while the other considers stagnation of the IR3 population and only IR4 sales in the year following the implementation of the new index. The difference between the consumption of the situations represents the energy saving, and the comparison of these values for different years of implementation was also part of the evaluation of this study. With estimated IR4 yields, an implementation in 2019 would lead to savings of approximately 0.82% of the PNEF 2030 target, which may not be as significant, but represents enough energy to power 109,000 houses for a year. The reduction in this energy saved by postponing the implementation of the new index could be more than half to a 4-year delay.
Monografia
Keywords: Motores industriais; População de motores; Teste de viabilidade técnicoeconômica; ENGENHARIAS::ENGENHARIA MECANICA